Ecological aspects of volatile organic compounds emitted by exotic invasive plants - Clavijo McCormick, Andrea; Effah, Evans; Najar-Rodriguez, Adriana (Frontiers in Ecology and Evolution, 2023)
Exotic invasive plants are present in almost all terrestrial ecosystems. Their spread and ability to colonize new habitats are predicted to increase with human travel, global trade, and climate change. These plants alter the environments they invade in multiple ways, affecting surrounding species. Chemically, invasive plants can modify their environment by releasing secondary metabolites such as root exudates (liquid) or airborne (gaseous) volatile organic compounds (VOCs). The allelopathic effect of invasive species’ root exudates is well studied and acknowledged as a trait contributing to invasiveness. However, less is known about the effects of invasive species’ VOCs, which are likely to play important ecological roles. Therefore, we conducted a systematic review of the literature during the last decade (2012-2022) to explore what is known about the ecological aspects of VOCs emitted by invasive plants, focusing on the factors affecting their emission (genetic, biotic, and abiotic), and their role on plant-plant and plant-insect interactions. We found 29 studies matching our search criteria. These studies suggest that invasive species are more ‘chemically diverse’ than their native counterparts and have different chemical behaviour in the native compared to the invaded ranges. The studies further highlight that chemical traits are heritable and contribute to invasiveness. Multiple biotic and abiotic factors affecting invasive plants’ VOC emission have been explored (e.g., herbivory, soil microorganisms, warming, and CO2). The studies indicate that invasive plants’ may experience less variation in their VOC emissions in response to environmental change than natives, with trade-offs between growth, reproduction and defence influencing VOC emissions. Regarding the impact on native species and their interactions, the allelopathic role of invasive plants’ VOCs on native plants is well documented, consistently showing phytotoxic effects. There is also evidence of their involvement in neighbour detection. While volatile-mediated interactions between invasive plants and native insects remain poorly studied, the existing evidence shows that invasive plant VOCs have the potential to disrupt communication between native plants and insects. But insects also use multiple cues to make foraging/oviposition decisions, compensating for the disruptive effect of invasive plant VOCs. To conclude, we identify knowledge gaps and propose avenues for future research.